Modern approaches to surgical treatment of acute pancreatitis (literature review) - A. I. Chavga; O. V. Midlenko; V. I. Midlenko; N. I. Belonogov; A. Sh. Khasanova; M. O. Zhdanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Acute pancreatitis, according to different authors, occupies up to 25 % in the structure of emergency surgical pathology of the abdominal organs. Remains quite high postoperative mortality. At present, the search for more effective approaches to determining the tactics of treating such patients and new effective, least traumatic surgical technologies continues. This review has been prepared in order to summarize information of modern approaches to the surgical treatment of acute pancreatitis. The review is based on the study and analysis of sources included in the electronic databases elibrary.ru, cyberleninka.ru and electronic versions of specialized publications that are freely available on the Internet. All authors state the need, along with general clinical studies, to use various methods of abdominal cavity imaging as early as possible. The use of ultrasound, magnetic resonance imaging and computed tomography, including with contrast, is recommended. The use of visualization allows to quickly clarify the diagnosis and choose the best tactics. Currently, most authors prefer percutaneous minimally invasive interventions performed under the control of various imaging methods. A combination of percutaneous and endoscopic technologies is also offered. These techniques allow, in most cases, with high efficiency to reduce the number of complications. Laparotomy has become much less commonly used, however, this access cannot always be refused. The tactics of treatment, including the choice of the method of operation, is carried out depending on the phase of the disease, the location of the focus, its delimitation from the surrounding tissues, the presence of concomitant pathology and complications. Staged surgical treatment with the initial use of minimally invasive techniques is preferred.